22 Emergency department litigation and coroner's inquests: a ten year analysis. Issue 12 (23rd November 2017) - Tilbury, Nicholas; Tabner, Andrew; Johnson, Graham
Abstract : Introduction: The burden of litigation within the NHS should not be underestimated. Indemnity costs rise in response to the rising frequency and costs of claims, with recent changes to the discount rate projected to increase NHS Litigation Authority (NHSLA) costs by £1 Billion per year. Litigation also has a significant psychological impact on staff. This study represents the first examination of litigation and Coroner's 'Prevention of Future Deaths' reports relating to emergency department care in the UK. Method: Using the Freedom of Information (FOI) Act (2000) we submitted data requests to both the NHSLA and the Ministry of Justice (MoJ). The NHSLA provided data concerning ED litigation claims between 2006 and 2015 including: Number of claims by year Number of successful and unsuccessful claims by year Number of settled claims Cost of claims (including defence costs, claimant costs and damages awarded) The MoJ provided data concerning PFD reports issued to EDs between 2006 and 2016. Data concerning PFD reports issued between 2012 and 2015 were extracted from the MoJ website. Data included: Report date Age and gender of the deceased Report summary Results: The total number of ED litigation claims made between 2006 and 2015 was 10, 040; 5745 (57.2%) resulted in a financial settlement. The number of claims successfully settled ranged from 382 in 2005/06 to 830 in 2014/15 with an upward trend throughout the decade. The mean cost of a successful claim was £114, 029; increasing from £66 754 in 2005/06 to £1 41 027 in 2014/15, a 111% increase. Delay/failure in diagnosis was the most common cause for litigation (4318 [44.5%]) and PFD reports (15 [21%]). A total of 70 PFD reports were issued within the study period; there was no trend in the number of reports issued per year. The greatest number of reports were issued in 2014 (18), far exceeding any other year. Discussion: Annual claim numbers have increased by 117% over the study period and mean claim cost has increased by 111% (far in excess of any rise expected due to inflation). Causation cannot be determined by this observational study, but potentially contributory factors include: the increasingly litigious nature of society in general; rising patient expectations and the worsening crisis in staff retention, recruitment and morale. This analysis of litigation patterns and PFD reports provides an insight that enables further focus on the underlying causes, subsequent improvement in patient care and a reversal of current litigation trends.